Analyzing the position of urf under the Islamic legal system in Malaysia - Ruzulan, Zulaipa; Ab Rahman, Suhaimi; Fathullah Harun, Hanifah Musa; Saidon, Rafeah; Ahmad, Thuraya (Medwell Publications, 2019)
Malaysia has been recognized as an Islamic country all over the years whereby it has robust Islamic legal system in order to cater with the challenging of contemporary issues. All in all, this research discusses the background of Islamic legal systems in Malaysia and the position of urf as one of the tools to address the contemporary issues. This is to show that Islamic legal system in Malaysia is progressive wherein it accepts and adopts any changes of legal rulings in line with the changing of time and places via. accommodating it with urf as an instrument to deduce legal rulings on related issues. Thus, this study involves a qualitative research methodology where the document analysis is used to collect the data and then, the data is analyzed by using content analysis and constant comparative techniques. In relation to this, the study found that urf plays important roles in the process of deducing legal rulings where the Islamic legal system framework can accommodate the rulings in line with the reality of the society. It is hope that, this study will benefit the policy makers and practitioners as well in dealing with a lot of Shariah issues.